A form of equations of motion of constrained mechanical systems - Sanh, Do (Vietnam Journal of Mechanics, 2002)
In the present paper a form of equations of motion of a constrained mechanical system is constructed. These equations only contain a minimum number of accelerations. In the other words, such equations are written in independent accelerations while the configuration of the system is described by dependent coordinates. It is important that the equations obtained are applied conveniently for. the mechanisms in which the use of independent generalized coordinates is not suitable.